Naturally Acquired Humoral Immunity Against Plasmodium falciparum Malaria - Gonzales, S. Jake; Reyes, Raphael A.; Braddom, Ashley E.; Batugedara, Gayani; Bol, Sebastiaan; Bunnik, Evelien M. (Frontiers in Immunology, 2020)
Malaria remains a significant contributor to the global burden of disease, with around 40% of the world’s population at risk of Plasmodium infections. The development of an effective vaccine against the malaria parasite would mark a breakthrough in the fight to eradicate the disease. Over time, natural infection elicits a robust immune response against the blood stage of the parasite, providing protection against malaria. In recent years, we have gained valuable insight into the mechanisms by which IgG acts to prevent pathology and inhibit parasite replication, as well as the potential role of IgM in these processes. Here, we discuss recent advances in our understanding of the mechanisms, acquisition, and maintenance of naturally acquired immunity, and the relevance of these discoveries for the development of a potential vaccine against the blood stage of Plasmodium falciparum.